Multinationality, Capital Structure, and Cost of Capital of Non-Financial Firm Listed on Indonesia Stock Exchange - Rezza Vitriya; Deddy Marciano (Relevance: Journal of Management and Business, 2020)
Multinational firms are firm that do business internationally, the higher degree of multinationality of a firm, they have more ability to get greater funding because there are more chances to get funding from foreign country. Because of that condition, multinational firms have different cost of capital with domestic firms. The main purpose of this study is to understand the impact of degree of multinationality, capital structure, firm size, profitability and growth opportunity to cost of capital. Panel data is used on this research and multiple linear regression analysis is used as analytical model. The result suggest that Indonesia multinational firms have lower cost of capital, cost of equity, and cost of debt than Indonesia domestic firms. The study found that capital structure is negatively related to cost of capital, this means that Indonesia multinational firm use more debt than Indonesia domestic firms, and so lower the cost of debt after tax and hence the cost of capital.